Intimate Partner Violence and Mental Distress, Post-Traumatic Stress Symptoms and Life Satisfaction in Colombian Women - Janneth E. Molina; M. Pilar Matud (Behavioral Sciences)
Intimate partner violence (IPV) against women is a major global public health and human rights issue, with significant consequences for women’s health and well-being. This study aimed to determine the relevance of IPV on women’s mental distress, post-traumatic stress symptoms and life satisfaction, and to examine whether age, education, socioeconomic status, social support and self-esteem are associated with mental health and well-being. The sample consisted of 255 women aged 18 to 71 living in Colombia who were assessed using six self-reported questionnaires. Hierarchical multiple regression analyses showed that more IPV was associated with women’s increased mental distress, post-traumatic stress symptoms and decreased life satisfaction. Although self-esteem and, to a lesser extent, social support were important predictors of women’s mental distress and well-being, psychological IPV was the main predictor of women’s post-traumatic stress symptoms, followed by lower self-esteem and younger age. The most important predictor of women’s mental distress was lower self-esteem, followed by more psychological IPV and lower social support. The main predictor of women’s life satisfaction was high self-esteem, followed by high social support, less psychological IPV and higher age and education. It is concluded that IPV, especially psychological IPV, is a serious threat to women’s mental health and well-being, while high self-esteem and, to a lesser extent, high social support are associated with better mental health and well-being.